Fixed Point Theorems for Mappings Contracting Perimeter of Triangles Embedded with F-Contractions in b-Metric Spaces (European Journal of Pure and Applied Mathematics, 2025)
In this article, the concept of a mapping contracting perimeter of triangles embedded with F-contractions in the framework of b-metric spaces is introduced. Some related fixed point results are established. Banach Contraction Principle is derived as a corollary of main result. Additionally, we construct examples of mappings contracting perimeters of triangles embeddedwith F-contractions which are not contraction mappings in the framework of b-metric spaces. The results of this article are the extensions of some already established results in literature
Keywords: fixed point (FP), Banach contraction principle (BCP), metric space (MS), $\mathsf{b}$-metric space ($\mathsf{b}$-MS), mapping contracting perimeters of triangle (MCPT)